2008
DOI: 10.32725/jab.2008.020
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant efficacy of flavonoid-rich fraction from Spermacoce hispida in hyperlipidemic rats

Abstract: Phytochemicals in fruits, vegetables, spices and traditional herbal medicinal plants have been found to play a protective role against many human chronic diseases including cancer and cardiovascular diseases. These diseases are associated with oxidative stress caused by excess of free radicals and other reactive oxygen species. Fractions rich in flavonoids obtained from S. hispida seeds were orally administered at three different doses of 20, 40 and 80 mg/kg BW to HFD fed rats. The antioxidant activity of a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…These cells produce antioxidants such as GPx to protect against ROS (Sadeghi et al 2008). ii) Sr was reported to be an effective scavenger for oxidative radicals and this antioxidant activity protects from damage and death (Kaviarasan et al 2008 ions like silica, calcium, phosphate, and sodium ions that contribute to a balanced oxidative status. That's why BG-Sr was more efficient than BG.…”
Section: Discussionmentioning
confidence: 99%
“…These cells produce antioxidants such as GPx to protect against ROS (Sadeghi et al 2008). ii) Sr was reported to be an effective scavenger for oxidative radicals and this antioxidant activity protects from damage and death (Kaviarasan et al 2008 ions like silica, calcium, phosphate, and sodium ions that contribute to a balanced oxidative status. That's why BG-Sr was more efficient than BG.…”
Section: Discussionmentioning
confidence: 99%
“…This high concentration obviously has a chance to undergo LDL oxidation and tocopherol‐mediated peroxidation because it enters into the artery wall (Osterud and Bjorklid 2003). Previous studies from our laboratory have showed that S‐Frf has antioxidant and antilipidperoxidative activity in HFD rats (Kaviarasan et al . 2008).…”
Section: Resultsmentioning
confidence: 94%
“…The two fractions were negative for polyphenols. Then, the defatted bulk residue was successively extracted by refluxing with ethyl acetate (1:3 w/v) (15 h twice) (Kaviarasan et al . 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts and plant enriched sources especially are considered suitable and easily available products for the prevention of these pathologies, as reported by e.g. Kaviarasan et al (2008).…”
Section: Introductionmentioning
confidence: 99%